The Effectiveness of The Addie Learning Model With the Assistance of Flat Shape Miniature Media on The Mathematics Learning Achievement of Grade V Students - Welu, Felix (Jurnal Ilmu Pendidikan dan Sosial, 2026)
The development of science and technology that is not matched by the facilities, infrastructure and skills of teachers in teaching school mathematics achievement resulted in the fifth grade students from year to year. Although this has been done to improve this problem, it has not been able to overcome it. So do other solutions by using the ADDIE model of media-assisted miniature flat wake. The problem is, is there a difference in learning achievement using the ADDIE model of media-assisted miniature flat wake with school performance using the conventional model? The study design was a pretest-posttest control group design. The instruments used are achievement tests and observation sheets student learning activities. The data analysis technique used in this study was a preliminary analysis using normality test and test for equality of two averages and final analysis using normality test and t-test. The result is that the initial analysis of both normal samples and the average are the same. While the final analysis both normal samples t-test and expressed taccount = 4.036> = 2.025 ttable so no difference in average mathematics achievement who received instruction using the ADDIE model of media-assisted miniature flat wake with the conventional model.